2021
DOI: 10.3389/fpls.2021.748146
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Wheat ZIP Gene Family and Functional Characterization of the TaZIP13-B in Plants

Abstract: The ZIP (Zn-regulated, iron-regulated transporter-like protein) transporter plays an important role in regulating the uptake, transport, and accumulation of microelements in plants. Although some studies have identified ZIP genes in wheat, the significance of this family is not well understood, particularly its involvement under Fe and Zn stresses. In this study, we comprehensively characterized the wheat ZIP family at the genomic level and performed functional verification of three TaZIP genes by yeast comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…With advancements in bioinformatics, an increasing number of ZIP members have gradually been discovered in various plant species, including Arabidopsis thaliana [17], cowpea (Vigna sinensis) [18], wheat (Triticum aestivum) [19], and potato (Solanum tuberosum) [20]. ZIP transporters are located primarily in the plasma membrane and on the membranes of various intracellular organelles [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advancements in bioinformatics, an increasing number of ZIP members have gradually been discovered in various plant species, including Arabidopsis thaliana [17], cowpea (Vigna sinensis) [18], wheat (Triticum aestivum) [19], and potato (Solanum tuberosum) [20]. ZIP transporters are located primarily in the plasma membrane and on the membranes of various intracellular organelles [58].…”
Section: Discussionmentioning
confidence: 99%
“…With advancements in whole-genome sequencing and bioinformatics, diverse types of ZIP proteins have been discovered in different plant species. In all, 16 ZIP genes have been authenticated in A. thaliana [17], 14 ZIP genes in Vigna unguiculata [18], and 58 ZIP genes in wheat (Triticum aestivum), 44 of which are homologous to rice ZIP proteins [19]. In potato (Solanum tuberosum), 29 ZIP genes have been identified [20] Selenium (Se) is a nonmetallic element classified in Group 16 of the periodic table along with sulfur (S), due to its similar chemical properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide analysis of a gene family is a way of rapidly and efficiently analyzing pathways to characterize gene functions and evolution [ 36 , 37 , 38 , 39 ]. In wheat, various genes are involved in drought, salt and metal stress responses by characterizing genes families [ 40 , 41 , 42 ]. In this study, 64 FKBPs were identified in the wheat genome by systematic in silico analysis ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We downloaded the complete genome sequence databases of lettuce from the NCBI database (Genome v7: ID:6720851) and downloaded the hidden Markov model (HMM) file of the ZIP domain (PF02535) from the Pfam protein family database (http://pfam.xfam.org/). The ZIP protein search was performed using the standard HMMER 3.0 software parameters from the Salad Gene database [30][31][32][33]. For the candidate genes obtained from the search, we used the SMART and PFAM programs to confirm that they contained specific domains, and manually removed ZIP genes that did not contain domains and duplicates [34,35].…”
Section: Identification and Database Source Of Lettuce Zip Gene Familymentioning
confidence: 99%